Mathematical Conceptions of the Elementary School Student- Teachers - Reginaldo Fernando Carneiro; Cármen Lúcia Brancaglion Passos (Universidade Federal do Rio Grande do Sul, 2014)
This paper aims to discuss the conceptions about mathematics of the Elementary School student-teachers of a Pedagogy distance learning course, in which we performed a qualitative research while working in the disciplines related to mathematics. The virtual activities generated data which analysis revealed some aspects of mathematics conception as problem solving. It also emphasized the need to guide the teaching in the understanding and rationale of formulae, procedures, and algorithms. In addition, it pointed out that the student-teachers had reflected on and problematized their conceptions.